Excess chemical potentials for hard atomic and diatomic solutes dissolved in hard-diatomic fluid - Banzragch, Tsednee; Tsogtbayar, Tsednee; Tsookhuu, Khinayat (Bulletin of the Institute of Chemistry and Chemical Technology, 2022)
An integral equation theory combined with Percus Yevick and Martynov-Sarkisov approximations has been applied for hard molecular solution in which the solutes are spherical and a tangent homonuclear diatomic dumbbell particles, and the solvent is a tangent homonuclear dumbbell fluid. At infinite dilution the excess chemical potentials for the solutes have been determined for reduced solvent densities of 0.1 to 0.9, and for diameter ratio values of the spheres of 0.5, 1, 1.5, and 2. Our findings for excess chemical potential have been compared with values obtained with analytical expression and Monte-Carlo data in literature. For the reduced densities less than 0.7, all values are in good agreement, however for higher densities than it the numerically obtained values from Martynov-Sarkisov approximation show better agreements with analytically obtained values and literature data than those from Percus-Yevick approximation. Хоёр атомт молекуляр уусгагчид ууссан нэг атомт, хос атомт уусагчдын илүүдэл химийн потенциал Хураангуй: Хатуу-бөмбөлөг потенциалт молекуляр уусмалд интеграл тэгшитгэлийн онолыг Перкус-Иевикийн болон Мартынов-Саркисовын ойролцоололд хэрэглэв. Энэ системд уусгагч нь шүргэлцсэн ижил-бөмбөлөгт молекуляр шингэн, харин уусагч нь нэг атомт ба хоёр-атомт шүргэлцсэн ижил-бөмбөлөгт молекуляр системүүд болно. Уусагч нь бүрэн ууссан үеийн уусагчийн илүүдэл химийн потенциалыг уусагч, уусгагчийн бөмбөлгийн диаметрийн харьцааны 0.5, 1, 1.5, 2 утгуудад уусгагчийн хураангуйлсан нягт 0.1–0.9 үед тооцоолов. Тооцоолсон үр дүнгээ аналитик болон Монте-Карло аргаар бодсон үр дүнтэй харьцуулахад нягт нь 0.7-аас бага үед илүү сайн тохирч байна. Харин нягт нь үүнээс их үед, тухайлбал, молекуляр уусагчийн хувьд Мартынов-Саркисовын ойролцоолол нь аналитик ба Монте-Карло аргын үр дүнд илүү дөхсөн үр дүн өгч байна. Түлхүүр үг: Перкус-Иевик, Мартынов-Саркисов, интеграл тэгшитгэл, Монте-Карло, бөмбөлөг, молекуляр шингэн